Edukasi dan Pemeriksaan Kesehatan Kelompok Lansia Melati untuk Mewujudkan Lansia SMART pada Masa Pandemi Covid-19 - Fitri Mailani; Rahmi Muthia; Emil Huriani; Sovia Susianty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Lack of information about Covid-19 issues also causes the elderly and their families to be afraid to visit health services due to being infected with Covid-19. Many elderly who have a history of chronic diseases such as hypertension, heart disease and diabetes were reluctant to carry out control at the Health Care Centre. The purpose of this service was to provide education regarding the transmission of Covid-19 and conduct health checks on the elderly of Melati Community related to chronic diseases. This activity was carried out with a personal approach by taking into account the health protocols of the pandemic. Educational activities and medical health checks were used for the elderly, such as TTV, blood sugar, cholesterol, uric acid, and nutritional status checks. These included outdoor exercise activities for the elderly. The community services activity team provided pocketbooks related to healthy elderly during the Covid-19 pandemic to help realize SMART (Healthy, Independent, Active, and Productive) for the elderly. The results of the examination showed that the elderly had hypertension at 45%, high uric acid at 35.4%, blood sugar levels above 200 as much as 9.2%, and high cholesterol at 80%. For that reason, older people must continue carrying out medical health checks periodically even though they are in a pandemic situation. Furthermore, the medical activity for the elderly has to involve their closest families, even carrying out independent checks at home in coordination with the availability of health workers in their zone.